Mediating Effects of Work Values on The Roles and Qualities of School Leaders and Teachers Core Behavioral Competencies - Lady Lyn Urriquia (Journal of General Education and Humanities, 2025)
The study investigates the mediating effects of work values on the roles and qualities of school leaders and teachers' core behavioral competencies. The research involved 100 public elementary school teachers from nine Del Remedio District, Division of San Pablo City schools, with the majority being female and married. The study used descriptive and correlational research methods to determine the relationship between leadership roles, qualities, and teacher performance. The questionnaire was divided into five parts: respondent profiles, perceptions about the mediating effects of work value in the roles and qualities of school leaders and teachers, and core behavioral competencies. The findings show a significant relationship between leadership roles and qualities and teacher performance and between teacher work values and performance in core behavioral competencies. Teachers' work values fully mediate this relationship. The study suggests that school leaders should be knowledgeable about their roles and qualities, provide necessary technical assistance, and prioritize professional growth for the benefit of the school. The Department of Education is actively working to develop these roles and qualities for better teacher performance.